An Investigation into the Differing Entry Modes Available and Internationalisation Process of an UK Web-based Firm, Internationalising into the US Market - Blundell, Lee R (2012)
This dissertation aims to provide an insight into the differing entry modes available to an UK Internet-based service firm and its internationalisation process. A case study was developed based on the international strategy of one of the leading specialist food comparison websites - Food Minus Allergies (FMA). Two key research questions are formulated to aid answering the fundamental investigation and these research questions prove very insightful and offer new perspectives on small firm internationalisation. Most of the best recognised theory in the industry, explaining the internationalisation of the firm is out of date and cannot therefore explain the internationalisation process of FMA. The majority of the different theories’ primary focus has been on the transfer of production inputs to different economies to take advantage of locational factors such as cheaper labour or access to raw materials. As FMA do not utilise these factors, some theory was unable to be applied to the business. The second research question offered three different hypotheses of how FMA could enter the US’ market. The different hypotheses consisted of 1) solely operating both the UK’ and US’ variants of the website from the UK, 2) investing in a physical structure in the US to conduct business activity, or finally 3) utilising a joint venture with a current US firm, to assist in learning about the market and improving a certain aspect of the business. Due to the nature of FMA’s business, where building relationships and maintaining them is of great importance, and also the importance of having control, it was recommended that FMA still choose to enter the US’ market with a physical structure but if they were to also opt for a joint venture, it should be critically analysed to determine how much control of their activities they will keep. Following the research, a new theory is proposed that aims to explain the internationalisation process of service-based internet firms such as FMA, and recommendations for FMA’s internationalisation are given.